Religiosidade, saúde e qualidade de vida: um olhar da pessoa idosa - Diniz, Ericka Ellen Cardoso da Silva (2019)
This study aims to understand the relationship of religiosity / spirituality with health and quality of life in elderly individuals, through the discourse of their relationship with faith as a factor of protection and support in various moments of life. It is a qualitative, descriptive, exploratory research, with narrative approach where content analysis was used to analyze the speech of the research subjects. The sample consisted of 30 elderly who were separated into two groups aiming at a differential of income and education in João Pessoa - PB. For data collection, a sociodemographic questionnaire and a semi-structured interview with questions about spirituality, religiosity, health and quality of life were used. The results of the content analysis showed that the elderly realized that religiosity / spirituality was seen as a contributing factor to good aging because it involves various aspects such as personal well-being, maintenance of emotional state and social interaction, all being related to good quality of life. In this regard, the higher income group reported having their personal well-being preserved regardless of religion, but what relationship with spirituality generated great satisfaction and well-being, while the low-income group showed a greater degree of importance, perceived in his life and also in religious social life. Thus, understanding the elderly individual, within a religious and spiritual context is essential demonstrating respect for their needs and reflecting how their attitudes and actions conclude that religiosity and spirituality have a positive impact on health and quality of life of the elderly.